Use of Info-Communicational Resources in Software Systems - Mkhitaryan, Andranik E.; Petrosyan, Arthur S.; Nanassian, Aram S. (Mathematical Problems of Computer Science, 2021)
The use of info-communicational resources in software systems is considered. The integration details and mechanisms of info-communicational resource UniMail into other systems are considered. Examples of software systems types, which could use the services of UniMail resource are discussed.